2019
DOI: 10.2147/ott.s188134
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNAs as potential molecular biomarkers in the clinicopathology and prognosis of cholangiocarcinoma: a systematic review and meta-analysis</p>

Abstract: BackgroundCholangiocarcinoma (CCA) is the second most common fatal primary hepatobiliary malignant carcinoma, characterized by early invasion and extremely poor outcomes. It is therefore necessary to identify a novel biomarker to better diagnose CAA and predict its prognosis. Recently, emerging evidence has revealed that some lncRNAs play an important role in the tumorigenesis and progression of CAA. In order to support this search for novel diagnostic and prognostic biomarkers for CAA, we conducted a meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…Secondly, besides mRNA, the predictive value of microRNA, lncRNA, and CpG in tumor prognosis had been validated. Multi-dimensional data analysis integrated with mRNA, microRNA, lncRNA, CpG might further increase the predictive efficiency [42][43][44]. Finally, cell functions and molecule mechanisms for the 7 mRNAs had not been explored in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, besides mRNA, the predictive value of microRNA, lncRNA, and CpG in tumor prognosis had been validated. Multi-dimensional data analysis integrated with mRNA, microRNA, lncRNA, CpG might further increase the predictive efficiency [42][43][44]. Finally, cell functions and molecule mechanisms for the 7 mRNAs had not been explored in our study.…”
Section: Discussionmentioning
confidence: 97%
“…A fixed-effects or random-effects model was applied to evaluate the prognostic value of Tiam1 expression and its association with lymphatic metastasis. A fixed-effects model was chosen when there was no obvious heterogeneity among studies 38 Otherwise, a random-effects model was used. Begg's test 39 and Egger's test 40 were employed to assess the publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for patients with CCA is abysmal due to late diagnosis and tumor resistance to chemotherapy and radiotherapy, emphasizing the need for new therapeutic targets and novel biomarkers [ 59 ]. Sun et al, reported that KCNQ1OT1 was highly expressed in CCA tissues and cells, and its overexpression was correlated with poor survival in CCA patients [ 27 ].…”
Section: Kcnq1ot1 In Human Cancersmentioning
confidence: 99%